Research of the Mechanism Design and Inverse Kinematics of a Novel Five-Axis Gantry Hybrid Machine Tool - Wang Junyan; Miao Hongbin; Ni Jing (Jixie chuandong)
A structure scheme for a novel 3T2 R gantry hybrid machine tool（ HMT） is proposed. In this scheme,a novel（ 3- RPR + R） &UPS parallel mechanism is proposed as the parallel processing module,which can realize four motion,with assistance of a direction linear guide,5- axis machining can be realized.Firstly,the three- dimensional translations and two- dimensional rotations motion of this machine tool are analyzed based on screw theory of motion and constraints. The DOF of the mechanism is calculated,and the driving joints are chosen. Then,the inverse position solution equation of the mechanism is built by using analytical vector method and the geometric relation. At last,the position inverse solution equation is solved by using MATLAB and the results simulation verification is carried out by using ADAMS,which verify that the correctness of the inverse displacement analysis model and the feasibility of the mechanism.